A tidy ending : a novel - Cannon, Joanna (Psychiatrist) (Scribner, an imprint of Simon & Schuster, Inc., 2022)
"Linda has lived in a quiet neighborhood ever since fleeing the dark events of her childhood in Wales. Now she sits in her kitchen, wondering if this is all there is--pushing the vacuum around and cooking fish sticks for supper is a far cry from the glamorous lifestyle she sees in the glossy catalogues coming through the mail slot addressed to the previous occupant, Rebecca. Terry isn't perfect--he picks his teeth, tracks dirt through the house, and spends most of his time in front of the TV. But that seems fairly standard--until he starts keeping odd hours at work, at around the same time young women in the town start to go missing. If Linda could track down and befriend Rebecca, maybe some of that enviable lifestyle would rub off on her. But the grass isn't always greener: you can't change who you really are, and criminals can hide behind closed doors"--